2000
DOI: 10.1017/s1355617700677019
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive and linguistic correlates of children's discourse after closed head injury: A three-year follow-up

Abstract: The discourse of 91 children who had sustained severe (n = 68) or mild (n = 23) closed head injury (CHI) was examined at least three years postinjury. The groups' retellings of a narrative story were analyzed according to two domains, information and language. In comparison to the mild CHI group, the severe group produced stories characterized by reduced content and information, impaired organization, fewer words, and less complex sentences. The relationships between discourse production and the group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
70
2

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(77 citation statements)
references
References 49 publications
5
70
2
Order By: Relevance
“…Channon & Watts (2003), again studying persons with TBI, found that a joint score made up of three executive functioning measures accounted for 36% of the variance seen in their discourse task. Similar findings have also been reported in children with TBI (Brookshire et al, 2000;Chapman et al, 2004).…”
Section: Evidence Of Crossoversupporting
confidence: 90%
“…Channon & Watts (2003), again studying persons with TBI, found that a joint score made up of three executive functioning measures accounted for 36% of the variance seen in their discourse task. Similar findings have also been reported in children with TBI (Brookshire et al, 2000;Chapman et al, 2004).…”
Section: Evidence Of Crossoversupporting
confidence: 90%
“…Specifically, difficulties in the pragmatic or contextual elements of language use have been described [Wiseman-Hakes et al, 1998], as well as deficits in discourse or language organization, such as reductions in the content or amount of information provided, impairments in overall language formulation, use of fewer words, and lower levels of complexity [Brookshire et al, 2000;Coelho, 2007]. Similar deficits in efficiency and completeness have been observed in the written language of children with ABI [Yorkston et al, 1997].…”
Section: Speech and Languagementioning
confidence: 97%
“…Difficulty with organizing story narratives is a deficit that emerges consistently following traumatic brain injury (TBI) (Body & Perkins, 2004;Brookshire, Chapman, Song, & Levin, 2000;Coelho, 2002). Story grammar measures that tap the organizational structure of stories (e.g., episodes) have been shown to be sensitive to TBI.…”
Section: Introductionmentioning
confidence: 99%